Undigested Pills in Stool Mimicking Parasitic Infection - Fazia Mir; Ilyas Achakzai; Jamal A. Ibdah; Veysel Tahan (Case Reports in Gastrointestinal Medicine)
Background. Orally ingested medications now come in both immediate release and controlled release preparations. Controlled release preparations were developed by pharmaceutical companies to improve compliance and decrease frequency of pill ingestion. Case Report. A 67-year-old obese male patient presented to our clinic with focal abdominal pain that had been present 3 inches below umbilicus for the last three years. This pain was not associated with any trauma or recent heavy lifting. Upon presentation, the patient reported that for the last two months he started to notice pearly oval structures in his stool accompanying his chronic abdominal pain. This had coincided with initiation of his nifedipine pills for his hypertension. He reported seeing these undigested pills daily in his stool. Conclusion. The undigested pills may pose a cause of concern for both patients and physicians alike, as demonstrated in this case report, because they can mimic a parasitic infection. This can result in unnecessary extensive work-up. It is important to review the medication list for extended release formulations and note that the outer shell can be excreted whole in the stool.